Optimization of tracer coating parameters and their effects on the mechanical properties and quality of food-grade tracers for grain traceability - Liang, Kun; Zhang, Lingling; Chen, Xiaohe; Shen, Mingxia (International Journal of Agricultural and Biological Engineering, 2019)
The purpose of this study was to optimize the coating process of food-grade tracers to manufacture tracers with good physical, mechanical and practical properties and an excellent appearance. The effects of the coating weight gain (1.00%-5.00%), coating solution spray rate (1.50-7.50 g/min) and tablet bed temperature (30°C-40°C) on the coating appearance quality, moisture absorption rate, friction coefficient, peak shear force, breaking rate, barcode recognition rate, transport wear rate and transport recognition rate were analysed using a Box–Behnken design (BBD) of response surface methodology (RSM). The experimental data were fitted to quadratic polynomial models by multiple regression analysis. The mathematical models of the barcode recognition rate, transport wear rate and transport recognition rate exhibited no statistically significant difference in these data. The optimum coating parameters were as follows: a 5.00% coating weight gain, spray rate of 5.47 g/min and tablet bed temperature of 35.42°C. Under the optimized conditions, the tracers had a good appearance (coating appearance quality), moisture resistance (moisture absorption rate), and frictional (friction coefficient), compression (peak shear force), and impact characteristics (breaking rate).Keywords: grain traceability, food-grade tracer, coating process, optimization, Box–Behnken designDOI: 10.25165/j.ijabe.20191202.4180Citation: Liang K, Zhang L L, Chen X H, Shen M X. Optimization of tracer coating parameters and their effects on the mechanical properties and quality of food-grade tracers for grain traceability. Int J Agric & Biol Eng, 2019; 12(2): 201–209.